2006
DOI: 10.1016/j.ymthe.2006.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of Sequential Administration of Recombinant DNA and Adenovirus Expressing L523S Protein in Early Stage Non-Small-Cell Lung Cancer

Abstract: L523S is an immunogenic lung cancer antigen that has demonstrated preclinical safety when the gene is injected intramuscularly as an expressive plasmid (pVAX/L523S) and when delivered following incorporation into an E1B-deleted adenovirus (Ad/L523S). We performed a phase I clinical trial in 13 stage IB, IIA, and IIB non-small-cell lung cancer patients. pVAX/L523S (8 mg on days 0 and 14 in all cohorts) and Ad/L523S (1, 20, 400 x 10(9) vp on days 28 and 56, cohorts 1, 2, and 3, respectively) were administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(34 citation statements)
references
References 16 publications
2
32
0
Order By: Relevance
“…In this regard, it is of interest to note that a phase I clinical trial with an immunotherapy targeting IMP3 in non-small cell lung cancer has been conducted. The results showed a high level of safety, but evidence of immune activation was limited; therefore, further clinical testing was suggested [29].…”
Section: Discussionmentioning
confidence: 98%
“…In this regard, it is of interest to note that a phase I clinical trial with an immunotherapy targeting IMP3 in non-small cell lung cancer has been conducted. The results showed a high level of safety, but evidence of immune activation was limited; therefore, further clinical testing was suggested [29].…”
Section: Discussionmentioning
confidence: 98%
“…This suggests that Ad5/3-Cox2L-D24, at the doses used here, did not induce acute systemic toxicity responses. 23,30 As proposed in previous investigations, [31][32][33] we analyzed Ad5/3-Cox2L-D24 genome copy number in the serum as a surrogate for viral replication. We found virus in the serum of 13 out of 17 patients at least once 2 days or later post treatment, and in 11/14 evaluable cases, the amount increased as compared to day 1.…”
Section: Discussionmentioning
confidence: 99%
“…Rapid clearance of adenovirus from the serum of humans has been shown in several studies, 9,10,24 which led to the proposal that virus detected at 2 days or later may be due to virus replication. [31][32][33] For example, DeWeese et al showed that intraprostatically administered oncolytic adenovirus disappeared from the blood within 12 h. Oncolytic Ad5/3-Cox2L-D24 in cancer patients S Pesonen et al…”
Section: Discussionmentioning
confidence: 99%
“…A phase I clinical trial of immunotherapy, targeting IMP-3 in non-small cell lung cancer, has been performed 26 . The present observations provide in vivo evidence that IMP-3 would also be a logical therapeutic target in gastric adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%